2020
DOI: 10.1002/cbic.202000119
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Molecule Study of Peptides with the Same Amino Acid Composition but Different Sequences by Using an Aerolysin Nanopore

Abstract: Nanopores are original sensors employed for highly sensitive peptides/proteins detection. Herein, we describe the use of an aerolysin nanopore to identify two similar model peptides, YEQYEQQDDDRQQQ (YEQ2Q3) and QDDDRQQQYEQYEQ (Q3YEQ2), with the same amino acid composition but different sequences. All‐atom molecular dynamics (MD) simulations reveal that YEQ2Q3 possesses fewer hydrogen bonds and a more extended conformation than Q3YEQ2. These two peptides, which fold differently, exhibit obviously distinct mass‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Further, when the signal to noise ratio is taken into consideration, WT AeL hardly discriminates the 20 natural amino acids according to these polymer labels with the volume exclusion model. Interestingly, previous studies revealed that short peptides with a length ranging from 6 to 14 amino acids could produce 7−10 times larger current blockage in comparison to the values estimated on the basis of the volume exclusion model 28,29 (Figure 1c and Table S5; all of the volumes of peptides were calculated from a previous study 30 ). Therefore, the simple volume exclusion model could not meet the requirements to describe the contributions of ionic current blockage.…”
mentioning
confidence: 79%
“…Further, when the signal to noise ratio is taken into consideration, WT AeL hardly discriminates the 20 natural amino acids according to these polymer labels with the volume exclusion model. Interestingly, previous studies revealed that short peptides with a length ranging from 6 to 14 amino acids could produce 7−10 times larger current blockage in comparison to the values estimated on the basis of the volume exclusion model 28,29 (Figure 1c and Table S5; all of the volumes of peptides were calculated from a previous study 30 ). Therefore, the simple volume exclusion model could not meet the requirements to describe the contributions of ionic current blockage.…”
mentioning
confidence: 79%
“…Aerolysin (AeL) nanopores [24,25] have also been employed for the structural discrimination of peptides. A series of peptides with different charges and lengths [26] and with the same amino acid composition but different sequences [27] were both discriminated by using AeL nanopores. In terms of the length of peptides, it has been shown that AeL nanopores could resolve the signal of poly-arginine with a length ranging from 10 to 5 amino acids, with the resolution of one arginine [28].…”
Section: Introductionmentioning
confidence: 99%
“…A complimentary direct observation technique may facilitate such interpretation. All atomistic Molecular dynamics (MD) has been used to understand conformational changes of protein inside nanopores [17][18][19] , translocation dynamics [20][21][22] , protein sensing 23 , which typically happen in a timescale of less than or of the order of 100 ns. Coarse grain models have also been used to investigate protein translocation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the interaction of the protein with the nanopore walls and the confinement effects of the nanopore may influence the motion of the protein molecule. In addition to influencing the dynamics of the protein, the confinement effect of the nanopore may cause structural changes in the protein molecule such as unfolding [17][18][19] . We will consider only the simplest case when the protein moves through the nanopore without any significant conformational changes 2 .…”
Section: Introductionmentioning
confidence: 99%